2021
DOI: 10.1007/s10653-021-01035-5
|View full text |Cite
|
Sign up to set email alerts
|

Are the soils and vegetation of a forest close to tailings ponds affected by metals and arsenic?

Abstract: This study aimed to determine the transfer of metals (Cd, Pb and Zn) and As to a Mediterranean forest close to five tailings ponds in Cartagena-La Union mining district (SE Spain). In addition, the effect of the rhizosphere of two native plant species, Olea europaea (OE) and Pistacia lentiscus (PL), on soil properties and chemical speciation of metal(oid)s was evaluated. Results showed there was no influence of the rhizosphere in the total concentration of metal(loid)s in soil, decreasing as Pb [ Zn [ As [ Cd.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(73 reference statements)
0
2
0
3
Order By: Relevance
“…Sahoo et al [ 55 ], by the review of a total of 117 relevant reports from 19 different countries such as India, Iran, Slovakia, Brazil, China, and Morocco, reported that in soil plus overburden samples taken near mining sites, maximum CF values for Fe, Zn, Cd, Pb, and As were 10.5, 28.8, 320, 34, 754, respectively. Martinez-Carlos et al [ 21 ] reported that As, Pb, Cd, and Zn exceed more than 10, 600, 40, and 80-fold the background level for natural soils in the study area located in the Cartagena-La Union mining district, Murcia Region (SE Spain), near the tailings ponds with a high concentration of Pb, Zn, Fe, Mn, or As.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sahoo et al [ 55 ], by the review of a total of 117 relevant reports from 19 different countries such as India, Iran, Slovakia, Brazil, China, and Morocco, reported that in soil plus overburden samples taken near mining sites, maximum CF values for Fe, Zn, Cd, Pb, and As were 10.5, 28.8, 320, 34, 754, respectively. Martinez-Carlos et al [ 21 ] reported that As, Pb, Cd, and Zn exceed more than 10, 600, 40, and 80-fold the background level for natural soils in the study area located in the Cartagena-La Union mining district, Murcia Region (SE Spain), near the tailings ponds with a high concentration of Pb, Zn, Fe, Mn, or As.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, plants used for phytoremediation need to effectively tolerate high concentrations of metal(loid)s, grow rapidly, and their root systems must be vigorous and show proper adaptability against a specific area [ 16 ]. Native plants, which can be found in wide geographical locations, are of particular interest in this perspective, since these spontaneous plant species are genetically adapted to the contaminant and, as such, can remove or retain it, reducing its toxicity in soil [ 15 , 21 ]. They could belong to a group known as hyperaccumulators, which can tolerate, absorb, accumulate, and translocate high levels of metal(loid)s, or excluder plants that can maintain relatively low levels in their shoot while still containing large amounts of metal(loid)s in their roots [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…En general, una de las características de los depósitos mineros localizados en el Distrito Minero de Cartagena-La Unión es la acumulación de concentraciones elevadas de metal(oide)s (Azizi et al, 2023;Martínez-Carlos et al, 2022;Shahrokh et al, 2023b), Concretamente, los metal(oide)s que presentaron mayor concentración en el conjunto de las parcelas analizadas en este estudio fueron el Zn y el Pb, seguidos de As y Cd (Figuras 4.3.1. y 4.3.2).…”
Section: Estudio De Los Metal/oides En Los Diferentes Tratamientosunclassified
“…Hay que destacar que, aunque los NGR utilizados en este estudio son de uso general y excluyen los suelos mineros, la comparación con los mismos es de utilidad para estimar el grado de enriquecimiento en metales que sufren estos suelos respecto de los naturales no mineros próximos a la zona de estudio. Concretamente, algunos estudios realizados por otros investigadores en la Sierra Minera de Cartagena-La Unión corroboran el importante enriquecimiento en metal/oides que sufren estos suelos (Gabarrón et al, 2018;Khademi et al, 2018;Martínez-Carlos et al, 2022).…”
Section: Estudio De Los Metal/oides En Los Diferentes Tratamientosunclassified
See 1 more Smart Citation